The effect of glucose supplements on exercise capacity in table tennis players - Dobosi, S.; Apostu, P.; Ochiana, N. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
Investigations were conducted on three groups of subjects table tennis players at the Olympic Center - Bistrita (n = 5 / group, age = 20.1 ± 0.5 years, G = 69.98 ± 0.3 kg, I = 173.5 ± 5.4 cm). Program effort, with the consent of the subjects, covered, for all lots: two weeks of specific training for 1 hour robot (machine throwing balls) with a frequency of 60 balls / min., with permanent change of directions of throw; robot is used for specific training in table tennis. Loads were studied: group I - control; group II - preload daily glucose, 250 ml of an aqueous solution with a concentration of 30% glucose, 2 hours prior to training; group III - day post-load glucose, 300 ml of an aqueous solution at a concentration of 40% glucose in 2 doses of 150 ml, 30 minutes and 60 minutes after the end of training. Determinations: indirect determination of aerobic capacity, pre- and post-training, 2 weeks after Astrand-Ryhming method; indirect determination of anaerobic exercise capacity, pre- and post-training, 2 weeks after the method used by the Center for Sports Medicine, Bucharest. Conclusions: Administration of glucose supplements to table tennis players train daily causes significant increases in aerobic and anaerobic exercise capacity, which can contribute to increased performance. Glucose supplementation pre- and post-effort, determined to improve predominant aerobic capacity.